2009
DOI: 10.1007/s10549-009-0661-1
|View full text |Cite
|
Sign up to set email alerts
|

Two founder BRCA2 mutations predispose to breast cancer in young women

Abstract: The mutation spectrum of BRCA1 and BRCA2 presents a wide range of unique mutations in breast/ovarian cancer patients but recurrent mutations with founder effects have also been described. BRCA2 5344delAATA and 9538delAA are recurrent mutations in Castilla-León (Spain) representing 10.6% of BRCA2 positive families. By genotyping eleven chromosome 13 markers (4.3 Mb) we demonstrate that each mutation shows core haplotypes of 1.66 Mb and 0.87 Mb, respectively, supporting a common ancestor in Castilla-León. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…These two frameshift variants are prevalent, representing 10.6% of BRCA2 positive families and have been linked to early-onset breast cancer. 30 In another study, four distinct BRCA1 mutations accounted for 72.7% of BRCA1-attributable breastovarian cancer in 104 families originated from the Centraleastern part of Tuscany. 31 Furthermore, BRCA2 c.7806-2A>T is a novel variant predicted to cause abnormal splicing 24 and is probably representing a specific settlement of colonists, 32 occurring as a single genomic event in Crete, approximately 800 years ago.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These two frameshift variants are prevalent, representing 10.6% of BRCA2 positive families and have been linked to early-onset breast cancer. 30 In another study, four distinct BRCA1 mutations accounted for 72.7% of BRCA1-attributable breastovarian cancer in 104 families originated from the Centraleastern part of Tuscany. 31 Furthermore, BRCA2 c.7806-2A>T is a novel variant predicted to cause abnormal splicing 24 and is probably representing a specific settlement of colonists, 32 occurring as a single genomic event in Crete, approximately 800 years ago.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to this, haplotype analysis revealed that the recurrent BRCA2 c.5146_5149delTATG and c.9310_9311delAA pathogenic variants are Spanish founders and all families originated from Castilla‐Leon. These two frameshift variants are prevalent, representing 10.6% of BRCA2 positive families and have been linked to early‐onset breast cancer . In another study, four distinct BRCA1 mutations accounted for 72.7% of BRCA1 ‐attributable breast‐ovarian cancer in 104 families originated from the Central‐eastern part of Tuscany …”
Section: Discussionmentioning
confidence: 99%
“…It was detected for the first time in northwestern Spain in Castilla y León [ 52 ] and has been described as a recurrent founder mutation in this region. Interestingly, it has been associated with EOBC (mean age 37.4 years; p = 0.033) [ 53 ]. Overall, this mutation has been identified in a group of eight independent Spanish families [ 53 55 ], and also in two Korean patients [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The response rate was even higher (64%) when the plasma concentrations of INCB7839 were above the IC 50 for HER2 cleavage. [104] INC7839 also improved progression-free survival in a subset of the patients expressing the p95 fragment of HER2. [105] The p95 fragment is a constitutively active portion of HER2 left (Right) Overlay of ADAM17 (magenta), ADAMTS-5 (blue) and MMP-9 (cyan), and ADAM22 (gray) structures shows sIVa-sIVb loop does not align with structures of other metzincins suggesting its uniqueness.…”
Section: Adam17mentioning
confidence: 99%